Analisis Berpikir Kritis Siswa dalam Pemecahan Masalah Matematika pada Siswa Bergaya Belajar Visual dan Auditori - Aliyah, Wasimatul; Purwaningsih, Wharyanti Ika (Jurnal Inovasi Pendidikan Matematika (JIPM), 2023)
The purpose of this study was to analyze the critical thinking skills of junior high school students in solving mathematical problems in terms of their learning styles, especially the two-variable linear system material. This type of research is qualitative research. Data collection techniques used critical thinking tests, interviews, and field notes. The subjects of this study were 2  class VIII students who were selected purposively, namely students with visual and auditory learning styles. The research instrument that became the main instrument was the researcher himself who was supported by a critical thinking test instrument for two-variable linear system material. The results of this study indicate that (1) The ability to think critically in solving mathematics problems in visual learning style students has met all the FRISCO critical thinking indicators (focus, reason, inference, situation, clarity, overview) in doing tests and interviews, because of the characteristics of this type. visual learning styles are better able to interpret mathematical objects visually before solving mathematical problems. (2) The ability to think critically in solving mathematical problems in auditory learning style students using the FRISCO critical thinking indicators (focus, reason, inference, situation, clarity, overview) two indicators are not met in the reason and overview indicators. Students with auditory learning styles still have the potential to develop their critical thinking skills, they just need a different treatment.